Age‐appropriate multidisciplinary approach to young children with cancer undergoing radiotherapy: The SIESTA procedure. Issue 1 (11th August 2020) - Clerici, Carlo Alfredo; Ferrari, Andrea; Pecori, Emilia; Diletto, Barbara; Alessandro, Ombretta; Pagani Bagliacca, Elena; Veneroni, Laura; Podda, Marta Giorgia; Poli, Andrea; Boni, Eleonora; Gasparini, Patrizia; Carabelli, Gabriele; et al.
Abstract: A standardized multidisciplinary step‐by‐step approach to improve the compliance of young (or difficult) children having to undergo radiotherapy was described and applied. The procedure is called SIESTA, which stands for show‐imagination‐evaluation‐support‐treatment‐anesthesia. Preliminary assessments suggest that the SIESTA approach was effective: the rate of young patients (≤6 years) requiring anesthesia decreased from 27% (14/52 cases) in 2011‐2012 (before the procedure was adopted) to 13% (6/46) in 2018.